2017
DOI: 10.1371/journal.pone.0170517
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive target capture/next-generation sequencing as a second-tier diagnostic approach for congenital muscular dystrophy in Taiwan

Abstract: PurposeCongenital muscular dystrophy (CMD) is a heterogeneous disease entity. The detailed clinical manifestation and causative gene for each subgroup of CMD are quite variable. This study aims to analyze the phenotypes and genotypes of Taiwanese patients with CMD as the epidemiology of CMD varies among populations and has been scantly described in Asia.MethodsA total of 48 patients suspected to have CMD were screened and categorized by histochemistry and immunohistochemistry studies. Different genetic analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Recent advances in -omics technologies have provided valuable tools for the diagnosis of NMDs and for the understanding of disease mechanisms at the molecular level (Butterfield, Dunn et al, 2017, Cummings, Marshall et al, 2017, Gama-Carvalho, M et al, 2017, Liang, Tian et al, 2017a, Liang, Tian et al, 2017b. In this study, we investigated the underlying mechanisms of rAAV-mediated correction of muscle pathology utilizing the canine model of X-linked myotubular myopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in -omics technologies have provided valuable tools for the diagnosis of NMDs and for the understanding of disease mechanisms at the molecular level (Butterfield, Dunn et al, 2017, Cummings, Marshall et al, 2017, Gama-Carvalho, M et al, 2017, Liang, Tian et al, 2017a, Liang, Tian et al, 2017b. In this study, we investigated the underlying mechanisms of rAAV-mediated correction of muscle pathology utilizing the canine model of X-linked myotubular myopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The second most common form encountered is the Ullrich type, with an estimated frequency of 7.2% in Japan . Liang et al suggested that the most common CMD in Taiwan might be the COL6‐related type . In 2017, a study from the UK population found LAMA2 ‐related CMD to be the most prevalent (37.4%), with 249 CMD cases, much more common than α‐dystroglycanopathies (26.5%), COL6‐related CMD (15.7%), SEPN1 (11.65%) and LMNA (8.8%) gene‐related CMDs.…”
Section: Discussionmentioning
confidence: 99%
“…26 Liang et al suggested that the most common CMD in Taiwan might be the COL6-related type. 27 In 2017, a study from the UK population 8 found LAMA2-related CMD to be the most prevalent (37.4%), with 249 CMD cases, much more common than α-dystroglycanopathies (26.5%), COL6-related CMD (15.7%), SEPN1 (11.65%) and LMNA (8.8%) gene-related CMDs. The recognition and hence incidence of CMD with glycosylation defects in α-dystroglycan has been increasing in European countries in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from the cohort of 23 patients with AC was extracted from the myocardial tissue samples using a QIAamp DNA Mini kit (Qiagen China Co., Ltd., Shanghai, China). The DNA sequence of these patients was screened by target capture sequencing, then verified by Sanger sequencing ( 14 , 15 ). All coding exons of the desmosomal genes (DSG2, NM_001943.3, DSC2, NM_024422.3, JUP, NM_021991.2, PKP2, NM_004572.3 and DSP, NM_004415.2) were enriched using custom-made SureSelectXT Target Enrichment arrays (Agilent Technologies, Inc., Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%